Health risk assessment of manganese in drinking water from gravity feed system among children of Orang Asli community - Mohd Sham, Shaharuddin; Yulyani, Vera; M, Haninah Fadiah (Environmental and Occupational Health Society, 2024)
Objective: Manganese is an essential element for humans; however, high exposure to humans can give adverse health effects, especially neurobehavioral problems among children. Manganese may enter the human body through ingestion of drinking water from sources that are not treated such as gravity feed systems. This study aims to determine the health risk from exposure to manganese in drinking water from gravity feed systems among children of Orang Asli in Ulu Chuai Village, Rembau, Negeri Sembilan. Method: A cross-sectional study design was conducted by collecting 38 samples of water from the household of Orang Asli Ulu Chuai Village to analyse the levels of pH and concentration of manganese in the drinking water. A questionnaire was used to interview 38 children aged 9 to 17 years old about their daily water intake and a weighing scale was used to measure their body weight. Result: All respondents (38) were using the gravity feed system as their water source and 92.1% of the children drink water that has been boiled while 7.9% directly drink from the pipes. The median level of manganese (0.20 mg/L) was above the NDWQS (0.1 mg/L) while the mean level of pH (6.87) was between the standard (6.5 – 9.0). There was no significant correlation recorded between manganese concentration and the pH level while the maximum HQ value (0.1185) obtained was below 1. Conclusion: High concentrations of manganese were found in the water from the gravity feed system; however, lower HQ values indicate no health risk was observed when the children consumed the water. Therefore, the water is considered safe, but actions need to be taken to ensure that the manganese concentration will not exceed the standards in the future.